A thematic review of the use of electronic logbooks for surgical assessment in sub-Saharan Africa. Issue 1 (February 2022) - Mooney, Ciaran; Mangaoang, Deirdre; O'Flynn, Eric; Bekele, Abebe; Tierney, Sean; Borgstein, Eric
Abstract: Introduction: Ensuring that surgical training programmes in low- and middle-income countries (LMICs) provide high quality training, including adequate operative experience, is of crucial importance in meeting the goals set out in the Lancet Global Surgery 2030. Electronic logbooks (eLogbooks) have been adopted to monitor both individual trainee progression and the performance of surgical training programmes. Methods: We performed a thematic review of the current evidence base surrounding the use of eLogbooks for the assessment of surgeons in training in sub-Saharan Africa, with a view to identifying the learning to date and areas for future research. Results: Whilst there are multiple papers highlighting the use of surgical eLogbooks in high-income countries, we identified only three papers which discussed their use in sub-Saharan Africa. Four common themes emerged which related to the use of surgical eLogbooks throughout sub-Saharan Africa: ease of analysis, centralised databases, discrepancies in reporting and technology limitations. Conclusions: Robust data to demonstrate trainee progression and the quality of surgical training programmes are of crucial importance in ensuring that surgical training programmes can rapidly scale up to deliver large numbers of well-trained surgical providers to address the unmet patient need in LMICs in the next decade. The limited data on the use of well designed, centralised electronic surgical logbooks indicate that this tool may play an important role in providing key data to underpin these training programmes. Highlights: eLogbooks are an part of monitoring surgical trainee and programme performance. eLogbooks allow for timely and centralised data on surgical training Use of eLogbooks has been limited in LMICs by technological difficulties Further research and investment is required to implement eLogbooks in LMICs